Sistem Agribisnis Pandan Wangi (Pandanus Amaryllifolius Roxb) di Subak Wasan Kemenuh, Desa Kemenuh, Kecamatan Sukawati, Kabupaten Gianyar - ADNYANA, I NENGAH SURATA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Pandan Wangi ( Pandanus Amaryllifolius Roxb ) Agribusiness System In Subak Wasan Kemenuh, Kemenuh Village, Sukawati Subdistrict, Gianyar Regency.  The pandan wangi commodity ( Pandanus Amaryllifolius Roxb ) has good prospects for development. This is because in Bali Province there are often religious ceremonies that use chopped pandan wangi to complete the canang. Agro-industry before marketing is very important considering that this fragrant pandan will have a higher selling value if it is marketed in chopped form ( keetan/kembang rampe). This research was conducted in Subak Wasan Kemenuh, Kemenuh Village, Sukawati District, Gianyar Regency. The population of this study were all farmers who carried out  pandan wangi farming after producing and making chopped pandan wangi leaves in the period June 2022 to June 2023, totaling 20 farmers. The sample was taken by census, the entire population was sampled, totaling 20 farmers. The aims of this research are (1) to analyze the provision of agricultural production facilities for pandan wangi, in Subak Wasan Kemenuh, Kemenuh Village, Sukawati subdistrict, Gianyar Regency; (2) analyzing the pandan wangi farming business, in Subak Wasan Kemenuh, Kemenuh Village, Sukawati Subdistrict, Gianyar Regency; (3) analyzing the productivity of shredded pandan wangi in Subak Wasan Kemenuh, Kemenuh Village, Sukawati Subdistrict, Gianyar Regency; (4) analyzing the income of shredded pandan wangi farmers in Subak Wasan Kemenuh, Kemenuh Village, Sukawati  Subdistrict, Gianyar Regency.The advice that can be given is from the aspect of providing agricultural production facilities, the presence of organic fertilizer and urea is more intensively prepared before planting pandan wangi. From the farming aspect, giving organic fertilizer and weeding needs to receive more attention in increasing the production of fragrant pandan which is good and sustainable.